2019
DOI: 10.1167/19.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Temporal attention improves perception similarly at foveal and parafoveal locations

Abstract: Temporal attention, the prioritization of information at a specific point in time, improves visual performance, but it is unknown whether it does so to the same extent across the visual field. This knowledge is necessary to establish whether temporal attention compensates for heterogeneities in discriminability and speed of processing across the visual field. Discriminability and rate of information accrual depend on eccentricity as well as on polar angle, a characteristic known as performance fields. Spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
77
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 67 publications
9
77
0
Order By: Relevance
“…Stimulus enhancement, signal enhancement, and noise exclusion each have distinct signatures depending on the amount of noise present in a display ( Figure 1 ). Notably, stimulus enhancement and signal enhancement both predict an improvement in perceptual sensitivity in the absence of noise, as has been reported in past studies of temporal attention ( Correa, Lupiáñez, et al, 2006 ; Denison, Heeger, & Carrasco, 2017 ; Fernández, Denison, & Carrasco, 2019 ; Nobre, Correa, & Coull, 2007 ; Nobre & Van Ede, 2018 ; Shalev, Nobre, & van Ede, 2019 ). However, because temporal attention studies have typically used noise-free displays, it is unclear whether temporal attention improves perception solely via stimulus enhancement or signal enhancement, or some combination of the proposed mechanisms.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Stimulus enhancement, signal enhancement, and noise exclusion each have distinct signatures depending on the amount of noise present in a display ( Figure 1 ). Notably, stimulus enhancement and signal enhancement both predict an improvement in perceptual sensitivity in the absence of noise, as has been reported in past studies of temporal attention ( Correa, Lupiáñez, et al, 2006 ; Denison, Heeger, & Carrasco, 2017 ; Fernández, Denison, & Carrasco, 2019 ; Nobre, Correa, & Coull, 2007 ; Nobre & Van Ede, 2018 ; Shalev, Nobre, & van Ede, 2019 ). However, because temporal attention studies have typically used noise-free displays, it is unclear whether temporal attention improves perception solely via stimulus enhancement or signal enhancement, or some combination of the proposed mechanisms.…”
Section: Introductionsupporting
confidence: 75%
“…Our ability to appropriately respond to dynamic and often noisy environments involves the recruitment of temporal attention, the allocation of attention to a moment in time ( Denison, Heeger, & Carrasco, 2017 ; Griffin, Miniussi, & Nobre, 2001 ; Lange, Krämer, & Röder, 2006 ; Milliken, Lupiáñez, Roberts, & Stevanovski, 2003 ; Nobre & Rohenkohl, 2014 ; Zokaei, Board, Manohar, & Nobre, 2019 ). A growing body of evidence has demonstrated that temporal attention improves perceptual detection and discriminability ( Correa, Lupiáñez, & Tudela, 2005 ; Correa, Lupiáñez, Milliken, & Tudela, 2004 ; Coull, Frith, Büchel, & Nobre, 2000 ; Fernández, Denison, & Carrasco, 2019 ; Griffin, Miniussi, & Nobre, 2001 ; Rohenkohl, Cravo, Wyart, & Nobre, 2012 ), which is thought to be mediated by improvements in early visual processing ( Correa, Lupiáñez, Madrid, & Tudela, 2006 ; Correa, Sanabria, Spence, Tudela, & Lupiáñez, 2006 ; Denison, Yuval-Greenberg, & Carrasco, 2019 ; Rolke & Hofmann, 2007 ). However, the computational mechanisms subserving these improvements in target detection and discriminability due to temporal attention remain unclear ( Nobre & Rohenkohl, 2014 ; Nobre & Van Ede, 2018 ; Weinbach & Henik, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that temporal expectations are supramodal is in line with the definition of expectation as regarding the prior probability for an event independent of the event's task relevance. The distinction between expectation and attention (related to the event's task relevance, which was constant in both conditions in this study) in the temporal domain 27,29,30 is based on the well-established distinction between expectation and attention in both the spatial 2,31,32 and the feature 2,33 domains. Supporting the distinction in the temporal domain, modulations of evoked potentials caused by visual-tactile temporal expectation precede those caused by modality-specific attention 34 .…”
Section: Discussionmentioning
confidence: 87%
“…The possibility that temporal expectations are supramodal is in line with the definition of expectation as regarding the prior probability for an event independent of the event’s task relevance. The distinction between expectation and attention (related to the event’s task relevance, which was constant in both conditions in this study) in the temporal domain 27,29,30 is based on the well-established distinction between expectation and attention in both the spatial 2,31,32 and the feature 2,33 domains. Supporting the distinction in the temporal domain, modulations of evoked potentials caused by visual-tactile temporal expectation precede those caused by modality-specific attention 34 .…”
Section: Discussionmentioning
confidence: 92%